The Ibanag teacher their characteristics, expressed professional problems and aspirations - Mangawil, Crispina Z. ([Quezon City s.n.], 1972)
The characteristics, problems, and aspirations of the Ibanag Elementary School teachers of Tuguegarao Districts I and II of Cagayan I were determined in this study.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers -- Tuguegarao, Cagayan